Anti-hypertensive effect of a novel angiotensin II receptor neprilysin inhibitor (ARNi) -S086 in DSS rat model - Sun, Jingchao; Xiao, Ying; Xu, Wenjie; Xing, Wei; Du, Frank; Tian, Maozhi; Xu, Danqi; Ren, Yihua; Fang, Xin (Frontiers in Cardiovascular Medicine, 2024)
Background: Angiotensin receptor-neprilysin inhibitor (ARNi), comprised of an angiotensin receptor blocker (ARB) and a neprilysin inhibitor (NEPi), has established itself as a safe and effective intervention for hypertension. S086 is a novel ARNi cocrystal developed by Salubris for the treatment of heart failure and hypertension.Methods: Dahl Salt Sensitive (DSS) hypertensive rat model and telemetry system were employed in this study to investigate the anti-hypertensive efficacy of S086 and compare it with the first ARNi-LCZ696.The study showed that oral administration of S086 dose-dependently lowered blood pressure (P<0.001). The middle dosage of S086 (23 mg/kg) exhibited efficacy comparable to LCZ696 (68 mg/kg), while also demonstrating superiority at specific time points (P<0.05). Notably, water consumption slightly decreased post-treatment compared to the vehicle group. Furthermore, there were significant increases in natriuresis and diuresis observed on the first day of treatment with 23 mg/kg and 68 mg/kg S086 (P<0.001). However, over the course of treatment, the effects in all treatment groups gradually diminished.This study demonstrates the anti-hypertensive efficacy of S086 in DSS hypertensive rat model, offering promising avenues for the clinical development of S086 as a hypertension treatment.